The relation of nasopharyngeal colonization by Streptococcus pneumoniae in comorbid adults with unfavorable outcomes in a low-middle income country - Juan Olivella-Gomez; Julián Lozada; Cristian C. Serrano-Mayorga; Lina Méndez-Castillo; Alejandro Acosta-González; André Emilio Viñán Garcés; Ingrid G. Bustos; Elsa D. Ibáñez-Prada; Yuli V. Fuentes; Ana M. Crispin; Erica Y. Garcia-Garcia; Eveling Santana; et al. (PLoS ONE, 2025)
Purpose Streptococcus pneumoniae (Spn) is the primary bacterial cause of lower respiratory tract infections (LRTI) globally, particularly impacting older adults and children. While Spn colonization in children is linked to LRTI, its prevalence, and consequences in adults with comorbidities remain uncertain. This study aims to provide novel data in that regard. Methods This prospective study of outpatient adults with chronic diseases was conducted in Colombia. Data on demographics, vaccination, and clinical history was collected in a RedCap database. Nasopharyngeal aspirate samples were examined for Spn colonization using traditional cultures and quantitative—real time polymerase chain reaction (q-rtPCR). Patients were followed for 18 months, with colonization prevalence calculated and factors influencing colonization and its impact on clinical outcomes analyzed through logistic regressions. Results 810 patients were enrolled, with 10.1% (82/810) identified as colonized. The mean (SD) age was 62 years (±15), and 48.6% (394/810) were female. Major comorbidities included hypertension (52.2% [423/810]), cardiac conditions (31.1% [252/810]), and chronic kidney disease (17.4% [141/810]). Among all, 31.6% (256/810) received the influenza vaccine in the previous year, and 10.7% (87/810) received anti-Spn vaccines. Chronic kidney disease (OR 95% CI; 2.48 [1.01–6.15], p = 0.04) and chronic cardiac diseases (OR 95% CI; 1.62 [0.99–2.66], p = 0.05) were independently associated with Spn colonization. However, colonization was not associated with the development of LRTI (OR 95%CI; 0.64 [0.14–2.79], p = 0.55) or unfavorable outcomes (OR 95% CI;1.17 [0.14–2.79], p = 0.54) during follow-up. Conclusions Chronic kidney and cardiac diseases are independently associated with Spn colonization. However, Spn colonization was not associated with LRTI/unfavorable outcomes in adult patients with chronic comorbidities in our cohort.